Biosynthesis of Lysosomally Escaped Apoptotic Bodies Inhibits Inflammasome Synthesis in Macrophages - Jiayi Mao; Wenzheng Xia; Yanglin Wu; Minxiong Li; Yun Zhao; Peisong Zhai; Yuguang Zhang; Tao Zan; Wenguo Cui; Xiaoming Sun (Research)
Hyperglycemia and bacterial colonization in diabetic wounds aberrantly activate Nod-like receptor protein 3 (NLRP3) in macrophages, resulting in extensive inflammatory infiltration and impaired wound healing. Targeted suppression of the NLRP3 inflammasome shows promise in reducing macrophage inflammatory disruptions. However, challenges such as drug off-target effects and degradation via lysosomal capture remain during treatment. In this study, engineered apoptotic bodies (BHB-dABs) derived from adipose stem cells loaded with β-hydroxybutyric acid (BHB) were synthesized via biosynthesis. These vesicles target M1-type macrophages, which highly express the folic acid receptor in the inflammatory microenvironment, and facilitate lysosomal escape through 1,2-distearoyl-sn-propyltriyl-3-phosphatidylethanolamine–polyethylene glycol functionalization, which may enhance the efficacy of NLRP3 inhibition for managing diabetic wounds. In vitro studies demonstrated the biocompatibility of BHB-dABs, their selective targeting of M1-type macrophages, and their ability to release BHB within the inflammatory microenvironment via folic acid and folic acid receptor signaling. These nanovesicles exhibited lysosomal escape, anti-inflammatory, mitochondrial protection, and endothelial cell vascularization properties. In vivo experiments demonstrated that BHB-dABs enhance the recovery of diabetic wound inflammation and angiogenesis, accelerating wound healing. These functionalized apoptotic bodies efficiently deliver NLRP3 inflammasome inhibitors using a dual strategy of targeting macrophages and promoting lysosomal escape. This approach represents a novel therapeutic strategy for effectively treating chronic diabetic wounds.